Rediscovery of the endangered Amphilophus lyonsi (Gosse 1966) (Cichliformes: Cichlidae) in Costa Rica; extended diagnosis and description and new ecological data - Angulo, Arturo; Gil-León, Jorge San; Oviedo-Soto, Alejandro; Abarca-Odio, Juan I.; Umaña-Villalobos, Gerardo (Zootaxa, 2022)
In this paper we report the rediscovery of the endangered cichlid fish Amphilophus lyonsi (Gosse 1966) in the southern Pacific region of Costa Rica. Additionally, we provide new and updated information on the morphology, growth, habitat use and distribution of the species based on data and specimens recently collected as well as on museum material. This information will be relevant for future taxonomic and conservation studies/purposes, contributing to a better understanding on the biology of the species.